(untitled) (Research, Society and Development, 2021)
The COVID-19 pandemic has caused an impact on both the professional-patient relationship and the routine of undergraduate dental students. Teledentistry arose presenting solutions for part of the new challenges. However, Teledentistry is not mandatory content in the dental curriculum. This study aimed to verify if Telehealth is being taught in Dental courses in the city of Sao Paulo. Between August and September of 2021, using data from the Brazilian Ministry of Education (e-MEC), the dental schools’ websites were checked. Information concerning the institution name, website existence, its curriculum, and the presence of a Telehealth or Teledentistry discipline were collected. It was found that 18, out of 21 dental courses were active (89% private institutions). Only five courses were offering Teledentistry/Telehealth as undergraduate content. In conclusion, the number of dental schools teaching telehealth in São Paulo is limited. Dental schools should capacitate the teaching staff and consider the mandatory curricular changes, due to the new National Guidelines, as a chance to correct the absence of Teledentistry as course content.